En quête du crétin ! - Pauline Hervois (Revue d'anthropologie des connaissances)
In the middle of the 19th century, people suffering from goiter and cretinism were the focus of medical concerns about the progression of these cripples and the origins of their deficiencies (intellectual and physical). These medical questions met with the infatuation with numbers that was characteristic of the period, and led to the setting up of data collections. This article analyzes the involvement of alienists in the construction of goitre and cretin numbers, from the 1790s to the 1870s, based on several administrative and scientific sources (medical surveys, population census, army recruitment). In particular, he analyzes the 1863 special survey on goiter and cretinism, from its genesis to publication of the results, and deconstructs and reconstructs the mechanisms involved in estimating the number of goiterers and cretins, a necessary step given the low response rate (15%). It also shows the techniques used to correct missing data.